'Alternative facts are not facts': Gaffe-announcements, the Trump administration and the media. (March 2019) - McVittie, Chris; McKinlay, Andy
Gaffes are actions or events that are treated as problematic in subsequent news coverage through the production of what we term here 'gaffe-announcements'. In an analysis of news media interviews conducted with members of the Trump administration during its first 100 days, we examine how interviewees respond to interviewer gaffe-announcements. Interviewees are seen to challenge the making of an announcement, to attempt to rework the ontological status of infelicitous talk, or to introduce the views of others who view the prior talk as felicitous. These responses lead in subsequent turns to reformulation of the gaffe-announcement, rejection of the response, or the views introduced being treated as irrelevant. These forms of response allow interviewees to avoid accepting that gaffes have occurred and allow the interviews to continue in line with normative expectations but discussion continues on matters that are treated as negative and detrimental to the interests of the administration.